HUBUNGAN ANTARA SELF RESILIENSI DENGAN MOTIVASI BERPRESTASI MAHASISWA PG PAUD ANGKATAN 2015 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Mardiana, Tri; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know whether there is levels and correlation between self resilience and achievement motivation in students early childhood education teacher program year 2015 faculty of education, Riau University. The samples of this research is the students early childhood education teacher program year 2015 faculty of education, Riau University that consists of 88 student, the sample of research are 68 students. Method of this research is Pearson Product Moment correlation to know the correlation between Self resilience and archievement motivation. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows ver. 17. Based of this research there is level of self resilience in the medium category with the percentage 72.3% and the level of achievement motivation in the medium category with the percentage 72.40%. Based of hypothesis there is any significant positive correlation between self resilience and achievement motivation in students early childhood education teacher program year 2015 faculty of education, Riau University. It could be seen from the result of correlation coefficient that rxy = 0.531 and significant level is 0.000 < 0.05. The level of correlation between self resilience and archievement motivation of of studentsis in the middle with the rank of determinant coefficient in the amount of KD = r² x 100% = 28.20%, it means that self resilience affect archievement motivation as much as 28.20%.Key Words: Self Resilience, Archievement Motivation